Delimiting the social boundaries of competition law in ASEAN: A common approach? - Ahamat, Haniff; Abdul Rahman, Nasarudin (2013)

(untitled)
Competition law is one of the key elements of the ASEAN Economic Community (AEC). As a precursor to the establishment of the AEC in 2015, all States Members of ASEAN have to introduce competition law in their national legal systems. As of now, Thailand, Indonesia, Vietnam, Singapore and Malaysia have put in place competition legislation enforced by the competition regulatory body of each respective country. Within the general conceptual framework, the aim of competition law should be to protect the process of competition, promote market efficiencies and enhance consumer welfare in the countries. Nevertheless there is a concern arising from the interface between the economic and social elements of competition policy considerations and framework. Competition law strives to ensure competition and economic efficiency but market structure and behaviour which harm competition or lead to inefficiency may have positive impact on the society. Competition law may exclude such situation or activity from the scope of the law or from liability provided by the law. On this note, this paper examines the social applications of competition legislation of Thailand, Indonesia,Singapore and more importantly Malaysia. Variations between different ASEAN Members are expected to influence any discussions on this issue but these variations may centre around the treatment of Small and Medium Enterprises (SMEs) in general by the law, the application of the law to sectors participated mainly by small holding producers (e.g. agriculture), the pursuit of distributive fairness as a possible objective of the law etc.